2019
DOI: 10.1016/j.ajpath.2019.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Biomarkers in the Urinary Peptidome of the Small Renal Mass

Abstract: Renal cell carcinoma (RCC) is often diagnosed incidentally as a small renal mass (SRM; pT1a, 4 cm). Increasing concerns surrounding the overtreatment of patients with benign or clinically silent SRMs has resulted in a recent shift in treatment recommendations, especially in elderly and infirm patients. There are currently no biomarkers that can predict progression. We used a quantitative label-free liquid chromatographyetandem mass spectrometry peptidomics approach and targeted parallel-reaction monitoring to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Additionally, our results indicated SPON2 expression could be used to stratifying patients as either low or high risk for recurrence, and the patients with high SPON2 expression had poorer RFS than those with low SPON2 expression. Tumor size and stage are the important prognostic factors [ 27 ]. However, the multivariate Cox model analysis indicated that tumor size and stage were not independent risk factors for RFS in patients with localized ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our results indicated SPON2 expression could be used to stratifying patients as either low or high risk for recurrence, and the patients with high SPON2 expression had poorer RFS than those with low SPON2 expression. Tumor size and stage are the important prognostic factors [ 27 ]. However, the multivariate Cox model analysis indicated that tumor size and stage were not independent risk factors for RFS in patients with localized ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, capillary electrophoresis and matrix-assisted laser desorption (MALDI) imaging approaches have been used as alternative methodologies, although their use is less common, likely due to the prevalence of LC-MS systems used for proteomics. By coupling high-performance liquid chromatography (HPLC) with high-resolution mass spectrometers, thousands of peptides can be monitored, while addressing the wide dynamic range of concentrations in complex biological samples …”
Section: Methodologies For Peptidomics Analysismentioning
confidence: 99%
“…Furthermore, given the possible association between circulating microRNA and cancer immunity, studies on circulating microRNA are expected to lead to the future development of new therapeutic agents through immunomodulation. MicroRNAs represent a new source of reliable biomarkers that can be diagnostic, prognostic, and predictive during therapy of cancer patients and has been widely studied in prostate [62], renal [63], and urothelial carcinoma [64]. MicroRNA can be quantified by reverse transcription-PCR (RT-PCR), Northern blotting, in situ hybridization, gene expression microarray, or NGS technology but also with commercially available isolation kits including the miRNeasy Mini kit (Qiagen) [65], ZR urine RNA isolation kit (Zymo Research) [66] for bladder cancer; Acid phenol-chloroform plus Silica columns (BioSilica Ltd.) [67], Urine Exfoliated Cell and Bacteria RNA Purification Kit (Norgen) [68] for prostate cancer; TRIZOL reagent (Invitrogen) [69] and miRNeasy Serum/Plasma kit (Qiagen) [70] for gastric cancer.…”
Section: Urinary Micrornasmentioning
confidence: 99%